Frieren : beyond journey's end. Volume 12 - Yamada, Kanehito (Shōnen Sandē komikkusu., 2025)
"Upon touching the ancient monument of the Goddess, Frieren finds herself cast back in time to 53 years before the death of Himmel the Hero. Her old adventuring comrades don't know she has come from the future, and Frieren realizes she must protect the secrecy of advancements in magic from their enemies. Here, the Demon King has not yet been defeated, and his minions are still powerful and determined to destroy Frieren!"--Publisher's website.